Potato consumption and risk of cardio-metabolic diseases: evidence mapping of observational studies. - So, Jisun.; Avendano, Esther E.; Raman, Gowri.; Johnson, Elizabeth J. (Tufts University. Tisch Library., 2020)
Keywords: Potato, French fries, Cardiovascular disease, Diabetes, Hypertension, Stroke, Epidemiology, Dietary pattern.; Springer Open.